SIKAP WARGA RW 028 TAMAN WISMA ASRI TERHADAP TAYANGAN IKLAN TELEVISI PUREIT PEMURNI AIR MINUM - Putra, Fajar Mulantoro (Universitas Prof. Dr. Moestopo (Beragama), 2012)
Advertising Pureit water purifier from PT. Unilever is titled a new technology purifying drinking water, and provide education on proprietary technologies that can be used to provide clean drinking water for domestic use. Pureit product presence will certainly lead to a variety of community attitudes or changes in drinking water. This study uses theory SOR (Stimulus - response) and Theory of Individual Differences (Theory of Individual Differences). This type of research used in this study is a quantitative descriptive format through propotionate Simple Random Sampling. The results showed RW. 028 on television commercials Pureit Water Purifier positive attitude. It can be seen from the respondents who tend to have attitudes like these ads. And the latter having been studied, there are differences in peopleâs attitudes toward television commercials Pureit based on educational background, occupation and age.